EXPLORATION AND EFFECTIVENESS OF BLACK BOX METHOD IN DEVELOPING EXPERIMENTAL OF VISUAL COMMUNICATION DESIGN LEARNING - Mohammad Rusnoto Susanto; Sugiyamin Sugiyamin (CILPA, 2016)
Experimental of visual communication design became one of the courses deepening of visual communication design. In the process of learning of experimental courses visual communication design through the application of its methodology process. Design methods known and continually introduced applicability through three methods: Glass Box Method, Black Box Method, and Self Organization. Black Box Method is a method that is applied in the design of technical learning project designed to explore creative ideas, concept design, artistic technique, presentation of the artistic design and value of the message through the visual language. It led this study to test the effectiveness of the Black Box Method exploration activities in learning and development of learning through the experimental process of visual communication design. The other objective of the reaearch is to recommend the Black Box Method as an alternative method to increase the effectiveness of the process of learning development of Experimental visual communication design.This is a qualitative research. Described the factual data findings reflectively regarding the learning process and the effectiveness of the Black Box Method found in the field. Purposive sampling was used to determe the subject of research, the instrument used in this study with the help of procedure method application process questionnaire, student worksheets, and the creation of visual communication design work to see the effectiveness of the method. Data collection procedures using a model of reflection (Reflection-in-Action) by Ralph (designing reflexively and intuitively). The degree of confidence (credibility) developed by Lexy J. Meleong is used to analyse the data through the process of checking the validity of the data.The researchers hope the results of this study were able to do a test of the effectiveness of Black Box Method exploration activities in the learning process and the development of learning through experimental visual communication design process. The researchers tried to convey the results of research which recommended Black Box Method as an alternative method in increasing the effectiveness of the process of learning development of Experimental vidual communication design.Â Keywords: exploration, affectivity, Black Box Method, Learning Development, and Eksperimental visual communication design